The Impact of Electronic Customer Relationship Management and Quality Moderated by Sharia Compliance on Loyalty: Study on Islamic banks in Jakarta - Rochmad, Rochmad (Journal of Finance and Islamic Banking, 2023)
In the rapidly digitizing landscape of Islamic banking, innovation is imperative for competitiveness and delivering top-tier services to customers. Electronic Customer Relationship Management (E-CRM) emerges as a key solution, streamlining interactions between banks and customers in the digital realm. This study delves into how E-CRM and Service Quality affect Customer Loyalty within Islamic banks, with a focus on Shariah Compliance as a moderating factor. The aim is to decipher how the Islamic banking sector can cultivate and enhance customer relationships in the digital age. Employing a quantitative approach, the research collects survey data from 212 Islamic bank customers through random sampling. Structural Equation Modeling (SEM), executed using IBM AMOS V.22 software, scrutinizes the collected data. Findings indicate a significant, positive contribution of E-CRM to Customer Loyalty. Interestingly, Service Quality doesn't wield a significant influence on Customer Loyalty, suggesting the presence of other influential factors in the Islamic banking arena. Notably, Shariah Compliance emerges as an important moderating element, bolstering the connection between Service Quality and Customer Loyalty, though it doesn't moderate the impact of E-CRM on Customer Loyalty.